1064 nm acoustic resolution photoacoustic microscopy. Issue 5 (21st January 2019) - Periyasamy, Vijitha; Das, Nandan; Sharma, Arunima; Pramanik, Manojit
Abstract : Photoacoustic imaging is a noninvasive imaging technique having the advantages of high‐optical contrast and good acoustic resolution at improved imaging depths. Light transport in biological tissues is mainly characterized by strong optical scattering and absorption. Photoacoustic microscopy is capable of achieving high‐resolution images at greater depth compared to conventional optical microscopy methods. In this work, we have developed a high‐resolution, acoustic resolution photoacoustic microscopy (AR‐PAM) system in the near infra‐red (NIR) window II (NIR‐II, eg, 1064 nm) for deep tissue imaging. Higher imaging depth is achieved as the tissue scattering at 1064 nm is lesser compared to visible or near infrared window‐I (NIR‐I). Our developed system can provide a lateral resolution of 130 μm, axial resolution of 57 μm, and image up to 11 mm deep in biological tissues. This 1064‐AR‐PAM system was used for imaging sentinel lymph node and the lymph vessel in rat. Urinary bladder of rat filled with black ink was also imaged to validate the feasibility of the developed system to study deeply seated organs. Abstract : High resolution, high‐depth acoustic resolution photoacoustic microscopy (1064‐AR‐PAM) was developed using 1064 nm light excitation. The near infrared—II wavelength enables deeper light penetration. The lateral resolution of the 1064‐ARPAM is 130 μm, axial resolution is 57 μm, and this system can image up to 11 mm deep in biological tissues. Sentinel lymph node, lymph vessel and urinary bladder were imaged in vivo using contrast agent with the developed set‐up.